Vietnamese People’s Naming Strategies Based on Vietnamese Tonation Characteristics - Bunchavalit, Patthida (Language and Linguistics, 2025)
This research aims to investigate the naming criteria of Vietnamese people based on changes in tone pitch, within the theory of Vietnamese tone phonetics proposed by Đoàn Thiện Thuật (2016) and Hoàng Thị Châu (2009); namely, the number of syllables, tonal contour, and pitch. The data were collected from 50 Vietnamese people living in Hanoi and residing in the Northern region of the Socialist Republic of Vietnam, consisting of 25 males and 25 females, divided into five generations based on their age every 20 years. The research found the number of syllables in Vietnamese names ranges from 3 to 4, with male names consisting of 3 syllables and female names ranging from 3 to 4 syllables. Vietnamese people prefer to use alternating type of tones, both in tonal contour type and pitch of each tone within the syllable. However, they tend not to use two-contour tones (T2) or single contour tones with a glottal stop (T3) placed together for more than two syllables. In addition, it is uncommon to name with high-level tones placed together for more than 3 syllables, especially with sắc and ngã, which are not typically placed together in more than two syllables, except for ngang. While low-level tones, such as huyền, hỏi, and nặng, are usually placed together in 3 to 4 syllables, the same tone is not typically placed together in more than 2 syllables. Therefore, Vietnamese names tend to have at least 2 tonemes but no more than 3. In other words, Vietnamese naming is based on the number of syllables and the characteristics of Vietnamese tones, with gender differences.